Studi Penggunaan Antiemetik pada Pasien Demam Tifoid Rawat Inap di RSUD Kabupaten Sidoarjo - Wardhani, Hety Setya; Surdijati, Siti; Hasmono, Didik (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2017)
Typhoid fever is an infection of the small intestine caused by Salmonella thypi bacteria with symptoms of fever at night. This disease is a contagious disease that can affect many people and is still a health problem, especially in developing countries. This study aims to analyze patterns of antiemetic use in typhoid fever patients. This research was conducted at Sidoarjo District General Hospital using a retrospective method in the period of January 1 to December 31, 2015. The sample was typhoid fever patients who were treated at the Sidoarjo District Hospital. The results obtained using the Health Medical Record (RMK) of patients who have been validated, 161 patients was detected and only 30 patients who is using antiemetic therapy. The antiemetic used is ondansetron. Ondansetron in single dose (3x4mg) iv used in 7 patients (23%) and (3x8mg) iv in 23 patients (77%). The duration of ondansetron use in typhoid fever patients in Sidoarjo District Hospital ≤ 2 days was 10 patients and ≥ 2 days was 20 patients. Antiemetics used were in accordance with the guidelines and no Drug Related Problems (DRPs) were obtained in typhoid fever patients as seen from their interactions with other drugs, the interval of administration, frequency of administration, duration of treatment, and dose of administration.